Atividade antimicrobiana in vitro de diferentes genótipos do óleo essencial Lippia gracilis Schauer frente a bactérias contaminantes de alimentos - Buarque, Paula Ribeiro (2013)
Lippia gracilis Schauer, Verbenaceae, is a small shrub with aromatic leaves found in semiarid regions of northeastern Brazil. It is popularly known as rosemary board and used to treat infections of the mouth, throat and skin. Some species contain in their chemical thymol and carvacrol, major compounds of known antimicrobial activity. To evaluate the in vitro antimicrobial activity of different chemotypes of essential oils extracted from plants Lippia gracilis Schauer genetically improved and their mixtures against bacteria contaminating food. The main components of chemotypes of Lippia gracilis Schauer were thymol, carvacrol, p-cymene, γ-terpinemo, 1,8-cineole, βcaryophyllene, myrcene, α-methyl terpinemo and thymol, carvacrol being the major component. The oils of Lippia gracilis Schauer LGRA 106, LGRA 107 e LGRA 110 at a concentration of 50 mL/mL presented the highest antimicrobial activity with inhibition zones between 9.3 and 10 mm on the bacteria Bacillus cereus (Gram +) and Serratia marcescens (Gram -). The oils LGRA 106 and 107 had the lowest MIC values of 0,78 mg/mL for Listeria monocytogenes and Bacillus subitilis. Pseudomonas aeruginosa is the only microbe that showed no inhibition at any of the tested chemotypes. Mixtures of oils LGRA106, and LGRA107 LGRA 110 increased the antimicrobial potential in relation to oils isolated, being the largest zones of inhibition (between 17 and 27 mm) obtained for the bacteria Staphylococcus aureus and Bacillus cereus. The greater inhibition observed for Bacillus cereus (inhibition of 27 mm) when used with LGRA106 50 µL, 100 µL of LGRA107 and 50 µL of LGRA110. The different chemotypes of Lippia gracilis essential oils, which were obtained from plants genetically improved, showed potential as an antimicrobial agent on the bacteria tested and conducting mixtures of oils can be an alternative to increase the power antimicrobial oils than used singly.